An organic-inorganic composite coating with stable protective performance and a preparation method thereof
The LDH film and silane/CeO2 composite coating are constructed on the surface of the aluminum alloy by one-step electrodeposition method, which solves the problems of complex process, long time and high energy consumption in the prior art, and achieves efficient and stable anti-corrosion and pollution-proof performance on the surface of the aluminum alloy.
Patent Information
- Application Number
- CN202310086220.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-01-18
AI Technical Summary
The prior art When preparing superhydrophobic coatings on aluminum alloy surfaces, the process is complex, time-consuming and energy-consuming, making it difficult to meet the stable demand for anti-corrosion and anti-fouling performance, especially in underwater precision instrument applications.
A rough structure LDH film and a low surface energy silane/CeO2 composite coating were synchronized on the surface of the aluminum alloy by one-step electrodeposition method, which simplifies the process flow and improves the bonding force between the coating and the substrate.
It realizes the preparation of aluminum alloy surface coating with simple process, short time and low energy consumption, and improves the anti-corrosion and anti-fouling stability and corrosion resistance of the coating, and is especially suitable for the protection of underwater precision instruments.
Smart Images

Figure CN115976593B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface treatment of aluminum alloys, and particularly relates to an organic-inorganic composite coating with stable protective performance and a preparation method thereof. Background Art
[0002] Aluminum and its alloys have excellent performance and are widely used in ships, aerospace, automobiles, home building materials, etc. However, its chemical properties are active, and it is very easy to undergo chemical reactions and corrosion failure during actual use; especially when it is used in underwater precision instruments in the marine environment, the large amount of marine organisms attached to the surface of the device will not only reduce its sensitivity and operability, but also accelerate the corrosion of the device and shorten its service life. Therefore, it is necessary to treat its surface with anti-corrosion and anti-fouling treatment. Superhydrophobic modification of the metal surface can not only effectively reduce the surface energy of the metal, shorten the residence time of the corrosive medium on its surface, and improve the corrosion resistance of the metal; it can also reduce the concentration of corrosive media in the metal surface coating, playing an anti-fouling / self-cleaning role. Therefore, superhydrophobic modification of the surface of aluminum and its alloys can effectively improve its anti-fouling and corrosion resistance.
[0003] Layered double hydroxides (LDH or LDHs) are a typical chemical conversion film. Since the LDH film is generated in situ on the surface of the metal substrate, it has good bonding with the substrate surface. At the same time, the LDH film also exhibits good physical barrier effect and ion exchange performance due to its unique layered rough structure, so it has received extensive attention in the field of metal corrosion protection. At the same time, the silanized coating on the metal surface is also widely used in the field of metal corrosion and antifouling due to its high chemical stability, good bonding with the substrate, green large-area preparation, and effective prevention of corrosive ions and oxygen from reaching the metal / corrosive medium surface.
[0004] The existing technology for preparing super-hydrophobic coatings on aluminum alloy surfaces mostly adopts a "two-step method" of "rough structure construction" and "low surface energy modification". The process of the "two-step method" is relatively complicated, time-consuming, and energy-intensive. Summary of the invention
[0005] One object of the present invention is to provide a method for preparing an organic-inorganic composite coating with stable protective performance on the surface of an aluminum alloy in view of the above technical problems. The entire preparation process is simple, time-saving and energy-saving. The prepared composite coating has high bonding strength with the aluminum substrate and good anti-corrosion and anti-fouling stability.
[0006] In order to achieve the above invention object, the present invention provides a method for preparing an organic-inorganic composite coating with stable protective performance, comprising the following steps:
[0007] S1: pre-treating the aluminum alloy substrate;
[0008] S2: placing the pre-treated aluminum alloy substrate in a precursor solution for a one-step electrodeposition treatment; the solute of the precursor solution is hexadecyltrimethoxysilane, tetraethyl orthosilicate, nickel nitrate, aluminum nitrate, potassium nitrate and cerium nitrate, and the solvent is a mixture of ethanol and deionized water;
[0009] S3: Cleaning and drying the surface of the aluminum alloy treated in step S2.
[0010] Compared with the prior art, the present invention adopts a one-step electrodeposition method to simultaneously construct a rough structure LDH film and a low surface energy compound silane / CeO2 composite organic-inorganic hybrid composite coating, which can simplify the coating method of the existing metal coating, increase the bonding force between the coating and the substrate, and has unique advantages, especially for precision devices with small size and complex shape. On the other hand, the layered LDH film layer and the low surface energy substance silane / CeO2 are synchronously generated by a one-step electrodeposition method, and the rough structure (LDH) and the low surface energy substance in the hybrid composite coating thus constructed can coexist for a long time, thereby avoiding changes in the structure and composition of the hybrid coating caused by external friction / wear, and thus avoiding changes in the hydrophobicity of the coating. In addition, CeO2 nanoparticles have excellent self-repairing properties, and adding CeO2 (cerium dioxide) to the hybrid coating is also conducive to improving the self-repairing and corrosion resistance of the coating.
[0011] Preferably, in step S2, the concentration of hexadecyltrimethoxysilane in the precursor solution is 10-40 mL / L, the concentration of tetraethyl orthosilicate is 5-30 mL / L, the concentration of nickel nitrate is 0.1-0.5 mol / L, the concentration of aluminum nitrate is 0.05-0.25 mol / L, the concentration of potassium nitrate is 0.1-0.4 mol / L, and the concentration of cerium nitrate is 0.05-0.2 mol / L; the volume ratio of the mixture of ethanol and deionized water in the solvent is V 乙醇 :V 水 =5.0~0.5.
[0012] Preferably, in step S2, the pH of the precursor solution is 5 to 10, the electrodeposition temperature is 20 to 30°C, and the electrodeposition time is 5 to 60 minutes.
[0013] Preferably, in step S2, the one-step electrodeposition is constant potential cathode deposition.
[0014] Preferably, the reference electrode of the constant potential cathode deposition is a saturated calomel electrode, the auxiliary electrode is a platinum sheet electrode, and the deposition potential is 1.0-5.0V.
[0015] Preferably, in step S3, hot air is used for drying, the hot air drying temperature is 60-120° C., and the drying time is 10-30 min.
[0016] Preferably, in step S1, the pretreatment includes preliminary coating, metallographic sandpaper polishing, degreasing, deionized water cleaning and cold air drying.
[0017] Preferably, in the early coating step, the aluminum alloy substrate is coated with nylon, exposing 5 cm 2 The aluminum alloy surface is used for later surface modification treatment and anti-corrosion and anti-fouling performance testing.
[0018] Preferably, after the preliminary coating step, the exposed aluminum alloy is polished with 800-grit sandpaper, and then degreased and cleaned with ethanol and deionized water.
[0019] The present invention also provides a LDH-silane / CeO2 composite hydrophobic coating with stable protective performance, which is prepared by the above-mentioned preparation method and has high bonding strength with the aluminum alloy substrate and good anti-corrosion and anti-fouling stability.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention successfully adopts the "one-step electrodeposition method" to prepare a hydrophobic LDH-silane / CeO2 composite coating on the surface of aluminum alloy, which simplifies the existing method steps of obtaining a hydrophobic coating on the surface of aluminum alloy by the "two-step method" of "building a rough structure" and "low surface energy modification".
[0022] (2) When preparing an organic-inorganic hydrophobic composite coating, this method has a simple preparation process and low energy consumption, and the performance of the coating can be simply controlled by various preparation parameters. Compared with the existing technology for preparing hydrophobic coatings, it can save energy and simplify the process.
[0023] (3) Compared with the hydrophobic coating obtained by the existing "two-step method", the LDH-silane / CeO2 composite coating obtained on the aluminum alloy surface by this method has better hydrophobic stability, that is, it exhibits better anti-corrosion and anti-fouling stability, and is particularly suitable for anti-corrosion and anti-fouling treatment of the surface of underwater precision instruments. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 These are the SEM images and contact angle images of the aluminum alloy surface coating prepared in Example 3 before and after wear.
[0025] Figure 2 Schematic diagram of sample wear experiment.
[0026] Figure 3The Nyquist diagram of the impedance diagram of the aluminum alloy surface coating prepared in Example 3 before and after being immersed in 3.5wt% NaCl for 20 days.
[0027] Figure 4 The impedance Bode diagram of the aluminum alloy surface coating prepared in Example 3 before and after being immersed in 3.5wt% NaCl for 20 days. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification or change based on the present invention will fall within the scope of the present invention.
[0029] Embodiment 1:
[0030] In this embodiment, the LDH-silane / CeO2 composite coating is prepared according to the following steps:
[0031] First, the exposed area is 5cm 2 The aluminum alloy substrate was polished with 800# sandpaper, and the polished aluminum alloy was degreased and cleaned with anhydrous ethanol and deionized water; then a mixed solution of ethanol and water (V 2 ) consisting of 10 mL / L HDTMS, 5 mL / L TEOS, 0.1 mol / L nickel nitrate, 0.05 mol / L aluminum nitrate, 0.1 mol / L potassium nitrate and 0.05 mol / L cerium nitrate was placed on the treated aluminum alloy substrate. 乙醇 :V 水 =5.0) for electrodeposition treatment; and adjusting the pH of the precursor solution to 5; using a constant potential cathode electrodeposition method, the reference electrode is a saturated calomel electrode, the auxiliary electrode is a large piece of platinum electrode, at a temperature of 20°C and a deposition potential of 1V, the electrodeposition treatment is performed for 5 minutes; finally, the composite coating on the surface of the aluminum alloy obtained in the above steps is placed in hot air at a temperature of 60°C and dried for 10 minutes.
[0032] Embodiment 2:
[0033] In this embodiment, the LDH-silane / CeO2 composite coating is prepared according to the following steps:
[0034] First, the exposed area is 5cm 2 The aluminum alloy substrate was polished with 800# sandpaper, and the polished aluminum alloy was degreased and cleaned with anhydrous ethanol and deionized water; then a mixed solution of ethanol and water (V 20 mL / L HDTMS, 15 mL / L TEOS, 0.2 mol / L nickel nitrate, 0.15 mol / L aluminum nitrate, 0.2 mol / L potassium nitrate and 0.1 mol / L cerium nitrate) was placed on the treated aluminum alloy substrate.乙醇 :V 水 =4.0) for electrodeposition treatment; and adjusting the pH of the precursor solution to 7; using a constant potential cathode electrodeposition method, the reference electrode is a saturated calomel electrode, the auxiliary electrode is a large piece of platinum electrode, at a temperature of 25°C and a deposition potential of 2V, the electrodeposition treatment is performed for 20 minutes; finally, the composite coating on the surface of the aluminum alloy obtained in the above steps is placed in hot air at a temperature of 80°C and dried for 20 minutes.
[0035] Embodiment 3:
[0036] In this embodiment, the LDH-silane / CeO2 composite coating is prepared according to the following steps:
[0037] First, the exposed area is 5cm 2 The aluminum alloy substrate was polished with 800# sandpaper, and the polished aluminum alloy was degreased and cleaned with anhydrous ethanol and deionized water; then a mixed solution of ethanol and water (V 20 mL / L of HDTMS, 20 mL / L of TEOS, 0.2 mol / L of nickel nitrate, 0.1 mol / L of aluminum nitrate, 0.4 mol / L of potassium nitrate and 0.2 mol / L of cerium nitrate) was placed on the treated aluminum alloy substrate. 乙醇 :V 水 =2.0) for electrodeposition treatment; and adjusting the pH of the precursor solution to 10; using a constant potential cathode electrodeposition method, the reference electrode is a saturated calomel electrode, the auxiliary electrode is a large piece of platinum electrode, at a temperature of 25°C and a deposition potential of 2V, the electrodeposition treatment is performed for 30 minutes; finally, the composite coating on the surface of the aluminum alloy obtained in the above steps is placed in hot air at a temperature of 120°C and dried for 30 minutes.
[0038] Embodiment 4:
[0039] In this embodiment, the LDH-silane / CeO2 composite coating is prepared according to the following steps:
[0040] First, the exposed area is 5cm 2 The aluminum alloy substrate was polished with 800# sandpaper, and the polished aluminum alloy was degreased and cleaned with anhydrous ethanol and deionized water; then a mixed solution of ethanol and water (V 2 mol / L) consisting of 30 mL / L HDTMS, 30 mL / L TEOS, 0.4 mol / L nickel nitrate, 0.2 mol / L aluminum nitrate, 0.2 mol / L potassium nitrate and 0.1 mol / L cerium nitrate was placed on the treated aluminum alloy substrate. 乙醇 :V 水=1.0) for electrodeposition treatment; and adjusting the pH of the precursor solution to 9; using a constant potential cathode electrodeposition method, the reference electrode is a saturated calomel electrode, the auxiliary electrode is a large piece of platinum electrode, at a temperature of 25°C and a deposition potential of 2V, the electrodeposition treatment is performed for 40 minutes; finally, the composite coating on the surface of the aluminum alloy obtained in the above steps is placed in hot air at a temperature of 80°C and dried for 20 minutes.
[0041] Example 5
[0042] In this embodiment, the LDH-silane / CeO2 composite coating is prepared according to the following steps:
[0043] First, the exposed area is 5cm 2 The aluminum alloy substrate was polished with 800# sandpaper, and the polished aluminum alloy was degreased and cleaned with anhydrous ethanol and deionized water; then a mixed solution of ethanol and water (V 2 ) consisting of 40 mL / L HDTMS, 30 mL / L TEOS, 0.5 mol / L nickel nitrate, 0.25 mol / L aluminum nitrate, 0.4 mol / L potassium nitrate and 0.2 mol / L cerium nitrate was placed on the treated aluminum alloy substrate. 乙醇 :V 水 =0.5) for electrodeposition treatment; and adjusting the pH of the precursor solution to 10; adopting a constant potential cathode electrodeposition method, the reference electrode is a saturated calomel electrode, the auxiliary electrode is a large piece of platinum electrode, at a temperature of 30°C and a deposition potential of 5V, the electrodeposition treatment is carried out for 60min; finally, the composite coating on the surface of the aluminum alloy obtained in the above steps is placed in hot air at a temperature of 100°C and dried for 10min.
[0044] Comparative Example 1
[0045] This comparative example is an AA6061 aluminum alloy sheet without any surface treatment.
[0046] Comparative Example 2
[0047] First, the exposed area is 5cm 2 The aluminum alloy substrate was polished with 800# sandpaper, and the polished aluminum alloy was degreased and cleaned with anhydrous ethanol and deionized water; then a mixed solution of ethanol and water (V 20 mL / L of HDTMS, 20 mL / L of TEOS, 0.2 mol / L of nickel nitrate, 0.1 mol / L of aluminum nitrate and 0.4 mol / L of potassium nitrate) was placed on the treated aluminum alloy substrate. 乙醇 :V 水=2.0) for electrodeposition treatment; and adjusting the pH of the precursor solution to 5; using a constant potential cathode electrodeposition method, the reference electrode is a saturated calomel electrode, the auxiliary electrode is a large piece of platinum electrode, at a temperature of 25°C and a deposition potential of 2V, the electrodeposition treatment is performed for 30 minutes; finally, the composite coating on the surface of the aluminum alloy obtained in the above steps is placed in hot air at a temperature of 120°C and dried for 30 minutes.
[0048] The difference between Comparative Example 2 and Example 3 is that no cerium nitrate solution is added to the precursor solution, and other parameters are consistent with Example 3.
[0049] Comparative Example 3
[0050] The LDH-silane composite coating on the surface of aluminum alloy was prepared by the traditional "two-step method", i.e., hydrothermal method combined with immersion method: First, the selected exposed surface area was 1 cm 2 The magnesium alloy electrode was polished with 1000# sandpaper, and then degreased and cleaned with acetone and secondary deionized water; the chemical conversion liquid was a mixed aqueous solution of 0.2 mol / L nickel nitrate and 0.1 mol / L aluminum nitrate, and the pH of the above solution was adjusted to 10 with 2 mol / L sodium hydroxide, and the conversion liquid and the magnesium alloy electrode were transferred to a hydrothermal reactor, and a 6061 aluminum alloy covered with an Al-Ni LDH film was prepared by a hydrothermal reaction at 150°C for 6 hours, and then the aluminum alloy covered with the LDH film was immersed in a 20 mL / L HDTMS ethanol solution for 30 minutes to obtain the LDH-silane composite coating on the surface of the aluminum alloy.
[0051] Structural characterization and performance testing:
[0052] In the above embodiments, embodiment 3 is the best embodiment. The surface morphology and contact angle of the LDH-silane / CeO2 composite coating on the aluminum alloy surface obtained in embodiment 3 after wear treatment were characterized. The results are as follows: Figure 1 The contact angle and rolling angle test data of other samples are shown in Table 1.
[0053] Table 1 Corrosion resistance of different samples before and after immersion in 3.5wt% NaCl for 20 days, and contact angle and rolling angle of different samples before and after wear at load 1N, test temperature 30℃, and friction length 200cm
[0054]
[0055] Depend on Figure 1 It can be seen that the LDH-silane / CeO2 composite coating on the aluminum alloy surface prepared by the one-step electrodeposition method in Example 3 presents a dense layered structure, that is, it presents a lamellar morphology unique to the LDH coating; and the contact angle of the coating is 153.7°, showing super hydrophobic properties ( Figure 1 A). Please also refer to Figure 2 , after the obtained coating sample was rubbed back and forth for a distance of 200 cm under a load of 1N and a temperature of 30°C, its surface still showed a layered structure, that is, a typical structure of LDH, indicating that the surface morphology of the coating did not change significantly before and after wear; at the same time, after wear, its contact angle decreased from 153.7° to 145.9°, and the contact angle decreased by 7.8°, that is, the coating changed from superhydrophobic to hydrophobic, but the degree of decrease in its contact angle was small ( Figure 1 B). The above test results indicate that the LDH-silane / CeO2 composite coating obtained in Example 3 has good mechanical wear resistance, ie mechanical stability.
[0056] Then, the sample obtained in Example 3 was immersed in a 3.5wt.% NaCl aqueous solution for 20 days and then subjected to an electrochemical impedance spectroscopy (EIS) test. At the same time, the sample in Example 3 that was not immersed was also subjected to an EIS test. The results are shown in FIG. Figure 3 and Figure 4 As shown. In the electrochemical impedance test: the test system is a three-electrode system, the aluminum alloy sheet obtained in Example 3 (including samples not soaked and soaked for 20 days) is the working electrode, the saturated calomel electrode is the reference electrode, and the platinum sheet is the counter electrode. The electrolyte solution used in the test is a 3.5wt.% NaCl aqueous solution, and the test and soaking temperatures are both 2522℃. Before the electrochemical impedance test, the open circuit potential E of the system is tested. ocp After the open circuit potential is stable, the EIS test is performed; the test range of EIS is 100kHZ~0.01HZ, and the amplitude is 10mV. The impedance value in the low-frequency zone is the corrosion resistance. In the electrochemical impedance spectrum, the impedance value in the low-frequency zone can represent the corrosion resistance of the sample in a specific medium. The larger the corrosion resistance, the better the corrosion resistance of the sample.
[0057] Table 1 lists the corrosion resistance before and after immersion, contact angle before and after wear, and rolling angle of different examples and comparative examples obtained according to the above method. Figures 3-4 As can be seen from the data in Table 1, the corrosion resistance of the sample in Example 3 decreased by one order of magnitude after immersion for 20 days, but its corrosion resistance can still reach 61533Ω·cm 2 , which is lower than the corrosion resistance of the untreated aluminum alloy sample before immersion (50520Ω·cm 2) are all large, indicating that the coating sample obtained by the method of Example 3 has good anti-corrosion stability; and the corrosion resistance of Examples 1 to 5 after immersion for 20 days is greater than that of the aluminum alloy without surface treatment (Comparative Example 1) after immersion, which also shows that the composite coating on the surface of the aluminum alloy obtained by the method of the present invention has good corrosion protection performance. In addition, according to the changes in contact angle and rolling angle before and after wear in Examples 1 to 5 in Table 1, it can be seen that the change rate of the contact angle and rolling angle of the samples in Examples 1 to 5 after external wear is smaller than that of the samples obtained by the traditional method (Comparative Example 3), which also shows that the composite coating obtained by this method has good mechanical stability.
[0058] In summary, compared with the hydrophobic coating prepared by the traditional "two-step method", the hydrophobic LDH-silane / CeO2 composite coating prepared on the surface of aluminum alloy by the "one-step electrodeposition method" in the present invention not only has a high bonding strength with the substrate and more stable anti-corrosion and anti-fouling properties, but also the method has a simple operation process, and the required equipment and environment do not involve high energy consumption problems such as long time and high pressure, so it has good application and promotion value.
[0059] The present invention is not limited to the applications listed in the specification and implementation modes, and can be fully applied to various fields suitable for the present invention. Without departing from the spirit and essence of the present invention, it is easy for those familiar with the art to implement other modifications and variations, but these corresponding modifications and variations should all fall within the scope of protection required by the present invention.
[0060] The above descriptions are only some embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that any solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a LDH-silane / CeO2 composite hydrophobic coating with stable protective performance, characterized in that: The following steps are involved: S1: pre-treating the aluminum alloy substrate; S2: placing the pre-treated aluminum alloy substrate in a precursor solution for constant potential cathode deposition treatment; the pH of the precursor solution is 5-10, the temperature of the electrodeposition is 20-30°C, and the time of the electrodeposition is 5-60 min; the solute of the precursor solution is hexadecyltrimethoxysilane, tetraethyl orthosilicate, nickel nitrate, aluminum nitrate, potassium nitrate and cerium nitrate, and the solvent is a mixture of ethanol and deionized water; the concentration of hexadecyltrimethoxysilane in the precursor solution is 10-40mL / L, the concentration of tetraethyl orthosilicate is 5-30mL / L, the concentration of nickel nitrate is 0.1-0.5mol / L, the concentration of aluminum nitrate is 0.05-0.25mol / L, the concentration of potassium nitrate is 0.1-0.4 mol / L, and the concentration of cerium nitrate is 0.05-0.2mol / L; the volume ratio V of the mixture of ethanol and deionized water in the solvent is 乙醇 :V 水 =5.0 ~ 0.5; S3: Cleaning and drying the surface of the aluminum alloy treated in step S2.
2. The preparation method according to claim 1, characterized in that: The reference electrode of the constant potential cathode deposition is a saturated calomel electrode, the auxiliary electrode is a platinum sheet electrode, and the deposition potential is 1.0-5.0 V.
3. The preparation method according to claim 1, characterized in that: In step S3, hot air is used for drying, the hot air drying temperature is 60-120° C., and the drying time is 10-30 min.
4. The preparation method according to claim 1, characterized in that: In step S1, the pretreatment includes preliminary coating, metallographic sandpaper polishing, degreasing, deionized water cleaning and cold air drying.
5. The preparation method according to claim 4, characterized in that: In the early coating step, the aluminum alloy substrate was coated with nylon, leaving 5 cm exposed. 2 The aluminum alloy surface is used for later surface modification treatment and anti-corrosion and anti-fouling performance testing.
6. The preparation method according to claim 5, characterized in that: After the preliminary coating step, the exposed aluminum alloy was polished with 800-grit sandpaper and then degreased and cleaned with ethanol and deionized water.
7. A LDH-silane / CeO2 composite hydrophobic coating with stable protective performance, characterized in that: The method is described in any one of claims 1 to 6.
Citation Information
Patent Citations
Super-hydrophobic aniline tripolymer modified SiO2 hybrid coating as well as preparation method and application thereof
CN107955959A
Aluminum alloy workpiece with layered double hydroxide-graphene oxide silane composite coating and preparation method of aluminum alloy workpiece
CN112553664A